Exome sequencing reveals low-frequency and rare variant contributions to multiple sclerosis susceptibility in Turkish families - Buyukgol, Furkan; Gurdamar, Berk; Aluclu, Mehmet Ufuk; Beckmann, Yesim; Bilguvar, Kaya; Boz, Cavit; Turanli, Eda Tahir (Nature Portfolio, 2025)
Multiple sclerosis (MS) is characterized as an immune-mediated central nervous system disease marked by chronic inflammation, demyelination, and progressive neurodegeneration. In this study, we evaluated the contribution of low-frequency and rare genetic variants to MS susceptibility within one of the largest family-based MS cohorts to date, comprising 215 individuals from 59 Turkish multiplex MS families. Whole exome sequencing was conducted on all samples including affected and unaffected members, followed by investigation of the effect of well-established human leukocyte antigen loci for MS on the elevated MS risk observed in our families. Subsequently, a gene-based burden analysis was performed on candidate genes identified through both our segregation analysis and existing literature. To prioritize the genes and pathways that are potentially associated with MS, a segregation-based analysis of the variants was conducted and complemented by gene-based pathway enrichment analysis. Our results highlighted the significance of the extracellular matrix in MS pathogenesis, as we identified laminin-related genes including LAMA5 and LAMB1 from both the segregation analysis and gene-based burden test. Hemidesmosome assembly emerged as a key pathway in our analysis, primarily driven by the identification of DST and PLEC as significant genes in the gene-based segregation analysis. Finally, we identified two rare coding variants passing our allele frequency and deleteriousness score-based filters, rs41266745 (C> T) in the CD109 gene with CADD phred score 24 and rs143093165 (T> G) in the ITPR1 gene with CADD phred score 22 and LOEUF 0.325, segregating within more than one family. Overall, this is one of the first and largest family-based MS studies from Turkey that features a unique cohort from an admixed population that enabled the detection of novel low-frequency and rare variants associated with MS. The findings from this study offer valuable insights that could guide future research aimed at further exploring and understanding the factors contributing to MS risk.
Keywords: Genetics; Familial multiple sclerosis; Blood-brain barrier; Whole exome sequencing